Kapasitas Petani Dalam Pengendalian Organisme Pengganggu Tanaman (Opt) Budidaya Kentang (Solanum Tuberosum L.) Di Kecamatan Argapura - Muhammad Hamzah Lubis; Thomas Widodo; Yoyon Haryanto (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
This study was conducted to describe the capacity of farmers, to determine the factors that affect the ability of farmers to control Plant Pest Organisms. Plant-disturbing organisms (OPT) such as pests, pathogens, and weeds cause problems in plant cultivation so that appropriate handling effort are needed. The application of pest control technology on potato plants in Argapura District has not been optimal. One of the reasons for this happening is the lack of information about the economic benefits of alternative pest control techniques other than synthetic pesticides. This study aims to describe the extent to which the capacity of farmers, analyze the factors that affect the capacity of farmers, and formulate strategies to increase the capacity of farmers in controlling plant pest organisms (OPT) in potato cultivation. The research sample was determined by purposive sampling technique, namely fifty-one potato cultivation farmers. The research variables consisted of farmer characteristics, external factors, and farmer capacity. The data analysis used in this research is descriptive statistical analysis and inferential analysis in the form of multiple linear regression. The results showed that the capacity of farmers in controlling plant pest organisms (OPT) in potato cultivation was in the medium category. The factors that affect the capacity of farmers are education, land area, and extension. Meanwhile, the factors that do not affect the capacity of farmers are age, farming experience, family dependents, infrastructure, farmer group activities, and access to information technology. The strategy is an effort to increase the capacity of farmers in controlling pests of potato cultivation in Argapura District is to increase group activities and counseling.